1967
DOI: 10.1002/tea.3660050403
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the concepts of physical and chemical change to elementary school children

Abstract: Replication of this study on instructional sequence and grade placement is in order. Do all children behave similarly in acquiring a concept of physical and chemical change?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1969
1969
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…A recent bibliography of research in students' misconceptions and alternative frameworks in science education by Pfundt and Duit (1988) specifically documented studies in chemical education. No studies were reported which identified students' understanding of electrochemistry, though Pfundt and Duit identified studies of students' understanding of the oxidation of steel wool (Anderson & Renstrom, 1982), chemical reactions (Anderson, 1984), chemical equilibrium (Buell & Bradley, 1972;Wheeler & Kass, 1978), thermodynamics (Johnstone, MacDonald, & Webb, 1977), the mole concept (Novick & Menis, 1976;Duncan & Johnstone, 1979), density and solubility (Gennaro, 1981), and physical and chemical change (Pella & Voelker, 1967;Voelker, 1975). Other studies have been reported on chemical equilibria (Hackling & Garnett, 1985;Gorodetsky & Gussarsky, 1986), stoichiometry and the mole concept (Novick & Menis, 1976;Mitchell & Gunstone, 1984), physical change (Cosgrove & Osborne, 1981), and chemical change (Schollum, 1981).…”
mentioning
confidence: 99%
“…A recent bibliography of research in students' misconceptions and alternative frameworks in science education by Pfundt and Duit (1988) specifically documented studies in chemical education. No studies were reported which identified students' understanding of electrochemistry, though Pfundt and Duit identified studies of students' understanding of the oxidation of steel wool (Anderson & Renstrom, 1982), chemical reactions (Anderson, 1984), chemical equilibrium (Buell & Bradley, 1972;Wheeler & Kass, 1978), thermodynamics (Johnstone, MacDonald, & Webb, 1977), the mole concept (Novick & Menis, 1976;Duncan & Johnstone, 1979), density and solubility (Gennaro, 1981), and physical and chemical change (Pella & Voelker, 1967;Voelker, 1975). Other studies have been reported on chemical equilibria (Hackling & Garnett, 1985;Gorodetsky & Gussarsky, 1986), stoichiometry and the mole concept (Novick & Menis, 1976;Mitchell & Gunstone, 1984), physical change (Cosgrove & Osborne, 1981), and chemical change (Schollum, 1981).…”
mentioning
confidence: 99%
“…The analysis of Figure 2 showed that dialogue in the relationship between teacher and students was characterized by open communication, through which not only were several students' responses heard during the resolution of the mathematical assignment, but also inferences were allowed, seeking to involve students in the discussion. The evaluation criterion rule is one of the discursive rules that not only influence, but also explain the students' results in the first moment, becoming even more efficient when the communication relationships between the subjects are open (PIRES; NEVES, 2004;FERREIRA, 2019).…”
Section: D) the Criteria For Evaluating Pedagogical Practicementioning
confidence: 99%
“…Os conceitos complexos equivalem aos conceitos abstratos definidos por Cantu e Herron (1978) como sendo aqueles que, ao contrário dos anteriores, não têm exemplos percetíveis ou, então, têm atributos definidores que não são percetíveis, como é o caso dos conceitos de fotossíntese e de respiração celular. Os temas unificadores dizem respeito a ideias estruturantes e correspondem, em ciências, às generalizações sobre o mundo que são aceites pelos académicos em cada área específica (Pella & Voelker, 1968) como, por exemplo, o tema "os organismos interagem com o ambiente, trocando matéria e energia" (Campbell & Reece, 2008, p. 6). As teorias científicas, como a teoria celular e a teoria da evolução, correspondem a explicações sobre uma ampla variedade de fenómenos relacionados e que já foram sujeitas a testagem significativa (Duschl, Schweingruber & Shouse, 2007).…”
Section: Análise Da Complexidade Do Conhecimento Científicounclassified